Pattern recognition for reliability assessment of water distribution networks : dissertation submitted in fulfilment of the requirements of the Board for Doctorates of Delft University of Technology and of the Academic Board of the UNESCO-IHE Institute for Water Education for the degree of doctor to be defended in public, on Monday, February 13, 2012, at 10:00 o'clock in Delft, the Netherlands /: dissertation submitted in fulfilment of the requirements of the Board for Doctorates of Delft University of Technology and of the Academic Board of the UNESCO-IHE Institute for Water Education for the degree of doctor to be defended in public, on Monday, February 13, 2012, at 10:00 o'clock in Delft, the Netherlands. (2012) - Unknown
No abstract available